Pegaga (Centella asiatica) - Bakhtiar, M. Taher (IIUM Press, International Islamic University Malaysia, 2016)
Centella asiatica (L.) (Family: Umbelliferae/Apiaceae) is commonly known as Asiatic pennywort and is known locally as pegaga. This herb has been consumed as medicine since ancient times especially in the Ayurverdic system of India and in folk medicine in China and Madagascar. Although in Malaysia Centella asiatica is also used by traditional healers as herbal remedies, but its popularity is more confined as a vegetable rather than a medicinal plant. The World Organization (WHO) has documented Centella asiatica as one of the most important medicinal plants to be conserved and cultivated. In Malay traditional practice, Centella asiatica has been applied externally to heal wounds. It is also used for cosmetic that can delay skin aging. Currently, pegaga is widely used incosmetics and skin care preparations. Previous studies on C. asiatica extracts have reported its potential as an antioxidant, antimicrobial agent, agent of collagen synthesis and even as a wound healer. Most studies report asiaticoside as the active constituent producing the said effect. In this book chapter, we attempt to provide more information on its phytochemical contents, extraction processes, antioxidant, in vitro wound healing property and medicated hydrogel formation based on studies done before.